The potential of Mythimna sequax Franclemont eggs for theproduction of Trichogramma spp. after cryopreservation in liquidnitrogen - Paixão, Magda Fernanda; Foerster, Luís Amilton; do Rocio Foerster, Marion (Revista Ciência Agronômica, 2023)
The cryopreservation of noctuid eggs in liquid nitrogen has proved be a promising tool in the mass production of Trichogramma, however studies into this technique have only just begun. This study evaluated the response of different densities of the female of Trichogramma pretiosum Riley to the parasitism of Mythimna sequax eggs stored and not stored in liquid nitrogen, and the performance of females reared only in cryopreserved eggs. The study evaluated the influence of the number of T. pretiosum females (4, 8 and 12) released to parasitise 40 M. sequax eggs, stored and not stored for 15 days in liquid nitrogen, as well as the performance of T. pretiosum females reared in eggs stored for three generations and females reared in non-stored eggs. Parasitism by T. pretiosum in stored eggs was 84%, twice the value obtained in previous studies. The emergence of parasitoids was greater than 95% in both experiments. The performance of females raised in stored eggs did not differ from that of females raised in non-stored eggs. The data show that the technique of cryopreservation of M. sequax eggs may be a viable alternative in the mass production of T. pretiosum.